2012
DOI: 10.1111/j.1742-1241.2012.02993.x
|View full text |Cite
|
Sign up to set email alerts
|

Type A behaviour: a reappraisal of its characteristics in cardiovascular disease

Abstract: Summary Aims:  The role of type A behaviour in cardiovascular disease is controversial and most of the research is based on self‐rating scales. The aim of this study was to assess the prevalence of type A behaviour in cardiology and in other medical settings using reliable interview methods that reflect its original description. Methods:  A sample of 1398 consecutive medical patients (198 with heart transplantation, 153 with a myocardial infarction, 190 with functional gastrointestinal disorders, 104 with canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 58 publications
2
26
0
2
Order By: Relevance
“…On the basis of original descriptions and the most relevant studies on type A, in the Diagnostic Criteria for Psychosomatic Research (DCPR) [71,72,73] nine items were identified to diagnose type A behavior. According to the DCPR, patients with cardiac conditions who presented type A (up to one third of the population) tended to display minimization of psychological impact and possible life-threatening consequences of cardiac disease [74]. This finding is in line with previous studies documenting an overlap between type A behavior and both hypomania and hyperthymic temperament, which are subclinical manifestations of the bipolar spectrum [75,76,77].…”
Section: Type a Behavior: A Reassessment Is Overduesupporting
confidence: 81%
“…On the basis of original descriptions and the most relevant studies on type A, in the Diagnostic Criteria for Psychosomatic Research (DCPR) [71,72,73] nine items were identified to diagnose type A behavior. According to the DCPR, patients with cardiac conditions who presented type A (up to one third of the population) tended to display minimization of psychological impact and possible life-threatening consequences of cardiac disease [74]. This finding is in line with previous studies documenting an overlap between type A behavior and both hypomania and hyperthymic temperament, which are subclinical manifestations of the bipolar spectrum [75,76,77].…”
Section: Type a Behavior: A Reassessment Is Overduesupporting
confidence: 81%
“…Next, it is possible that the participants of our study had some intensified personality characteristics compared to general populations, given longstanding suggestions of associations between personality traits and risk of coronary heart disease (Rosenman et al, 1976;Sirri et al, 2012). For example, type A behavior is more prevalent in patients with cardiovascular disease compared with other medical disorders (Sirri et al, 2012). Finally, the timing of the personality assessment could give rise to different results.…”
Section: Discussionmentioning
confidence: 96%
“…The vulnerable type may be associated with poor outcome because the FFM model of personality shares generic risk factors with depression (Kendler and Myers, 2010), which has a greater genetic overlap in men than women (Fanous et al, 2007). Next, it is possible that the participants of our study had some intensified personality characteristics compared to general populations, given longstanding suggestions of associations between personality traits and risk of coronary heart disease (Rosenman et al, 1976;Sirri et al, 2012). For example, type A behavior is more prevalent in patients with cardiovascular disease compared with other medical disorders (Sirri et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of cardiovascular disease, the impetus for this was the observations by both Osler [62] in 1912 and later Meyer Friedman [63] that a type A personality, characterized by worry over time, hostile cynicism, and work pressures, is a risk factor for cardiovascular disease. Sirri et al [64] have carefully reviewed the current conceptualization of this construct [65]. There is clear data that behavioral therapy as well as medication such as buspirone can change elements of type A personality but the long-term outcomes from such interventions are not known [66,67,68].…”
Section: Figmentioning
confidence: 99%